2023
DOI: 10.1172/jci164317
|View full text |Cite
|
Sign up to set email alerts
|

HSV-2 triggers upregulation of MALAT1 in CD4+ T cells and promotes HIV latency reversal

Abstract: HSV-2 coinfection is associated with increased HIV-1 viral loads and expanded tissue reservoirs, but the mechanisms are not well-defined. HSV-2 recurrences result in an influx of activated CD4+ T cells to sites of viral replication and an increase in activated CD4+ T cells in peripheral blood. We hypothesized that HSV-2 induces changes in these cells that facilitate HIV-1 reactivation and replication and tested this hypothesis in human CD4+ T cells and 2D10 cells, a model of HIV-1 latency. HSV-2 promoted laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Consistent with these observations, a recent study reported upregulation of MALAT1 concomitant with HIV reactivation in 2D10 cells by another HDACi, romidepsin [33 ▪ ]. When MALAT1 was knocked out, the ability of romidepsin to induce latency reversal in 2D10 cells was reduced [33 ▪ ].…”
Section: Noncoding Rnas and “Shock And Kill” Treatmentssupporting
confidence: 62%
See 3 more Smart Citations
“…Consistent with these observations, a recent study reported upregulation of MALAT1 concomitant with HIV reactivation in 2D10 cells by another HDACi, romidepsin [33 ▪ ]. When MALAT1 was knocked out, the ability of romidepsin to induce latency reversal in 2D10 cells was reduced [33 ▪ ].…”
Section: Noncoding Rnas and “Shock And Kill” Treatmentssupporting
confidence: 62%
“…An example of LRAs inducing HIV reactivation, in part, via modulation of ncRNAs is the upregulation of MALAT1 with the concomitant reduction of the LTR occupancy by EZH2 following treatment with either phytohemagglutinin-P (PHA-P) or SAHA [42]. Consistent with these observations, a recent study reported upregulation of MALAT1 concomitant with HIV reactivation in 2D10 cells by another HDACi, romidepsin [33 ▪ ]. When MALAT1 was knocked out, the ability of romidepsin to induce latency reversal in 2D10 cells was reduced [33 ▪ ].…”
Section: Noncoding Rnas and “Shock And Kill” Treatmentsmentioning
confidence: 69%
See 2 more Smart Citations
“…Significantly, epidemiological research suggests a synergistic effect between HSV and HIV infections, with HSV infection in HIV patients being associated with increased HIV-1 viral load and disease progression (Looker et al, 2017, Calistri et al, 2003, Heng et al, 1994). Some studies have further unveiled the ability of HSV to activate HIV latent reservoirs (Amici et al, 2004, Amici et al, 2001, Pierce et al, 2023). Given the potential of HSV to simultaneously induce antigen-specific immune responses and reactivate latent viral reservoirs, we propose a proof-of-concept strategy to achieve an HIV functional cure using a modified bifunctional HSV-vectored therapeutic vaccine.…”
Section: Introductionmentioning
confidence: 99%